Microneedle-array patches loaded with dual mineralized protein/peptide particles for type 2 diabetes therapy - Wei Chen (Nature Portfolio, 2017)
Diabetes treatments often rely on frequent and scheduled drug administration, which reduces patient compliance and increases treatment cost. Here, the authors develop a microneedle-array patch that separately loads drug-releasing module and glucose-sensing element for on-demand, long-term diabetes therapy.